1970
DOI: 10.1111/j.1365-2621.1970.tb00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Food Preferences of College Students and Nutritional Implications

Abstract: SUMMARY— The food preferences of approximately 50,000 college students representing 1% of the college enrollment in the United Stares during the 1966‐1967 school year were analyzed. The responses were collected on a regional basis, subdivided as to sex and were reported as national and regional totals. Two hundred and seven food items were surveyed. Foods were ranked in terms of percent Liked, Disliked and Do Not Know. Median and percentile groupings for each food class, as well as for all foods, were calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 3 publications
5
24
0
Order By: Relevance
“…Even though the importance of culture in food choice is obvious, psychology has paid little attention to cultural differences in liking for different foods (Rozin, 1996). We know that different cultures tend to eat different foods (Hillman, 1979;Revel, 1982), and that people like the foods in their own cuisine more than those found only in other cuisines (Einstein & Hornstein, 1970). However, we know very little about differences in liking for foods that are common and part of the cuisines of several different cultures.…”
mentioning
confidence: 98%
“…Even though the importance of culture in food choice is obvious, psychology has paid little attention to cultural differences in liking for different foods (Rozin, 1996). We know that different cultures tend to eat different foods (Hillman, 1979;Revel, 1982), and that people like the foods in their own cuisine more than those found only in other cuisines (Einstein & Hornstein, 1970). However, we know very little about differences in liking for foods that are common and part of the cuisines of several different cultures.…”
mentioning
confidence: 98%
“…As in other preference studies (Vawter & Konishi, 1958;Meiselman & Waterman, 1978;Einstein & Hornstein, 1970;Viljoen, 1995), it was found that bread and baked products were rated high-preference items. All the groups rated all types of bread as well as vetkoek as high-preference items (median values of five and higher).…”
Section: Bread and Baked Productsmentioning
confidence: 48%
“…With the exception of the Xhosas, the groups rated Horlicks a highpreference item. Fresh milk, as in other preference studies (Vawter & Konishi, 1958;Schuck, 1961;Einstein & Hornstein, 1970;Meiselman & Waterman 1978;Viljoen, 1995), received the highest preference rating of all the evaluated items. The black ethnic groups rated sour milk (maas), maghew and buttermilk high-preference items, whereas the whites and coloureds rated them as low or neutral preference items respectively.…”
Section: Beveragesmentioning
confidence: 84%
See 2 more Smart Citations